2022
DOI: 10.1007/s12072-022-10445-1
|View full text |Cite
|
Sign up to set email alerts
|

The clinical implications and molecular features of intrahepatic cholangiocarcinoma with perineural invasion

Abstract: Background Perineural invasion (PNI) is associated with metastasis in malignancies, including intrahepatic cholangiocarcinoma (ICC), and is correlated with poor prognosis. Methods The study included three large cohorts: ZS-ICC and TMA cohorts from our team, MSK cohort from a public database, and a small cohort named cohort 4. Prognostic implications of PNI were investigated in MSK cohort and TMA cohort. PNI-related genomic and transcriptomic profiles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Our RNAseq results also showed significant differential expression of EFGR ( p = 0.03, |log2FC|= 0.38) and genes related to EGF pathway ( PRKCA, JAK1, PLCG1, p = 0.01, 0.02, 0.02 and |log2FC|= 0.32, 0.20, 0.16, respectively) in PNI patients, although prognosis was not significant. Higher frequency of KRAS mutations were found in intrahepatic cholangiocarcinoma patients and colon cancer with PNI 14 , 15 , coincide with RNAseq results in Fig. 2 b.…”
Section: Discussionsupporting
confidence: 87%
“…Our RNAseq results also showed significant differential expression of EFGR ( p = 0.03, |log2FC|= 0.38) and genes related to EGF pathway ( PRKCA, JAK1, PLCG1, p = 0.01, 0.02, 0.02 and |log2FC|= 0.32, 0.20, 0.16, respectively) in PNI patients, although prognosis was not significant. Higher frequency of KRAS mutations were found in intrahepatic cholangiocarcinoma patients and colon cancer with PNI 14 , 15 , coincide with RNAseq results in Fig. 2 b.…”
Section: Discussionsupporting
confidence: 87%
“…While our study focuses on early-stage ICC patients without further postoperative adjuvant therapy, existing literature has reported that PNI-positive ICC patients exhibit insensitivity to postoperative chemotherapy ( 10 ). However, following combined immunotherapy, the prognosis of PNI-positive postoperative patients is superior to that of negative patients ( 18 , 19 ). ICC, characterized by a poor prognosis, despite numerous studies suggesting various approaches to improve outcomes ( 20 - 23 ), still lacks a standardized and effective treatment.…”
Section: Discussionmentioning
confidence: 98%
“…This study validated previous work that early ICC patients with PNI had higher rates of more severe jaundice, cholangitis, HBV infection, CA199, serum albumin, and platelet count, all of which were believed to be closely connected with ICC patients’ prognosis ( 27 - 32 ). Moreover, PNI is closely associated with the pathological malignancy phenotype of ICC, with patients exhibiting PNI often accompanied by large duct-type and lymph node metastasis ( 19 ). Furthermore, PNI may serve as a substitute for biological markers of invasive disorders that reflect tumor or stage-specific characteristics substantially.…”
Section: Discussionmentioning
confidence: 99%
“…PNI is an independent risk factor for CCA and has been considered a worse prognostic factor in CCA [ 14 ]. In addition, a negative PNI has been considered a reference for postoperative chemotherapy in some studies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%